Probing Bidirectional Plasmon‐Plasmon Coupling‐Induced Hot Charge Carriers in Dual Plasmonic Au/CuS Nanocrystals (Small 12/2023). Issue 12 (22nd March 2023) - Bessel, Patrick; Niebur, André; Kranz, Daniel; Lauth, Jannika; Dorfs, Dirk
Abstract : Dual Plasmonic Au/CuS Nanocrystals Au/CuS nanocrystals show two separated localized surface plasmon resonances (LSPRs) at different wavelengths. In article number 2206379, Jannika Lauth, Dirk Dorfs, and co‐workers observe a hot charge carrier relaxation from both LSPRs regardless which LSPR is excited resonantly. This transient hot charge carrier response from a non‐excited LSPR is not known to literature and leads to a deeper understanding of interaction of LSPRs.